The significance of nitrification for oceanic new production - Yool, Andrew; Martin, Adrian P.; Fernández, Camila; Clark, Darren R. (Nature, 2007)
Nitrogen does the rounds Some 16% of the original Amazon forest has been cleared for agriculture, but much of that land is no longer in use and is starting to regrow. Such 'secondary forests' are becoming increasingly important as tropical land-use change results in larger areas that have gone through agricultural phases. A new study of Amazon forest areas between 3 and 70 years into their recovery reveals nitrogen and phosphorus cycling processes consistent with large losses of nitrogen during land use change. Nitrogen availability is ephemeral, and readily disrupted by either natural or anthropogenic disturbance. Understanding how the nutrient cycling processes of secondary forest succession should contribute to the better management Amazonian ecosystems. Elsewhere in the nitrogen cycle, an analysis of virtually all extant data on open oceanic nitrification, in conjunction with a global ecosystem model, demonstrates that the generally accepted assumptions concerning its distribution are incorrect. Much of the nitrate taken up by the oceans is generated through recent nitrification near the surface and, at the global scale, nitrification accounts for about half of the nitrate consumed by growing phytoplankton. This means that many previous attempts to quantify marine carbon export may be significant overestimates. This study synthesizes data from several published datasets to provide a global estimate of the impact of nitrification on oceanic new production. The flux of organic material sinking to depth is a major control on the inventory of carbon in the ocean 1 . To first order, the oceanic system is at equilibrium such that what goes down must come up 2 . Because the export flux is difficult to measure directly, it is routinely estimated indirectly by quantifying the amount of phytoplankton growth, or primary production, fuelled by the upward flux of nitrate 3 . To do so it is necessary to take into account other sources of biologically available nitrogen. However, the generation of nitrate by nitrification in surface waters has only recently received attention. Here we perform the first synthesis of open-ocean measurements of the specific rate of surface nitrification 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 and use these to configure a global biogeochemical model 13 , 14 to quantify the global role of nitrification. We show that for much of the world ocean a substantial fraction of the nitrate taken up is generated through recent nitrification near the surface. At the global scale, nitrification accounts for about half of the nitrate consumed by growing phytoplankton. A consequence is that many previous attempts to quantify marine carbon export, particularly those based on inappropriate use of the f -ratio (a measure of the efficiency of the ‘biological pump’), are significant overestimates.